Temporal Trends in Syphilis Epidemiology in the UAE: A Five-Year Retrospective Analysis (2018-2022) - Khatoon Hossein Mehdi Poor, Nargis; Mohamed Jasim Ali AlDabal, Laila; Mostafa Hamed, Dujana; Adhnon, Arshiya; Mohammad Ali Ahmad, Alanood; Mohammad Abdulla Saif Al Suwaidi, Shamsa; Mohammad Sharif Seddigh, Laleh; Nooruddin Abdulwahid Kazim, Mahra; Lavina Dsouza, Carol; Moosa, Musthafa (International Journal of Sexually Transmitted Diseases, 2024)
Objectives This study examined the frequency and dynamics of syphilis in the United Arab Emirates (UAE) between 2018 and 2022. Recognizing the significance of understanding syphilis trends, this study intends to conduct further research on sexually transmitted diseases in the context of the UAE. Methods This was a retrospective cross-sectional study. This study focused on patients who underwent syphilis screening between January 2018 and December 2022. Cases were classified as conclusive only if they passed the first screening and subsequent confirmatory tests. Results The findings demonstrate that Syphilis frequency varied throughout the UAE during the study period. Demographic trends and sex variations were discovered, providing insight into how syphilis patterns change. Additionally, this study identified a broad spectrum of clinical manifestations, confirming the complexity of the disease. It was also noted that males had a higher frequency of syphilis than females. Conclusion Understanding the complexity of the frequency of syphilis is critical for developing effective public health interventions. Variations in frequency, demographic trends, sex disparities, and clinical manifestations indicate the need for personalized preventive and control measures. This study provides important information that may be utilized to motivate focused initiatives to address the difficulties associated with syphilis in the UAE, thus enhancing overall public health.
Keywords: Syphilis; United Arab Emirates; Retrospective; Sexually Transmitted Diseases; Screening